Professores dos anos iniciais do ensino fundamental e livros didáticos de matemática - Glaucia Marcondes Vieira (2013)
In the quest to understand the pedagogical practices of teachers of the early years of elementary school and the way they use their mathematics textbooks, we proposed in this research to listen closely,through interviews, the point of views of ten teachers who work in public and private schools of Belo Horizonte. With theoretical and methodological foundations in Oral History, we transcribed and textualized the employees narratives, which constitute the empirical material of this study. The analysis of this material led to the formation of two thematic units related to the usage of textbooks: Math textbooks for teaching practices and Math textbooks for Math teachers training. Considering that the math teacher seeks specialized training to teach mathematics, these two thematic units will conflict, influence and complement each other, making it impossible to recognize them as disjoint paths or categories. These two units of analysis guided us towards what each single teaching experience had shown, the detected peculiarities that we called unities, which deals with elements related to the uses of math books that converge in their own teaching practices, (re) signifying themselves. Finally, we discuss what was possible to conclude from the understanding that the elements that constitute the teaching practices regarding mathematics textbooks, undertaken in various contexts, enforce singular practices linked to possible contradictions that come from the textbooks narratives. These conclusions may point the way for future investigations and improvements on Math teaching.